Kekerasan Terhadap Anak dan Relevansinya dengan Pemberian Hukuman Dalam Mendidik Anak - Rosmawati Rosmawati (At-Ta'lim : Media Informasi Pendidikan Islam, 2015)
Implementation of Cooperative Learning Method Jigsaw on material type History Islamic Propagation motivated by problems of poor learning outcomes of students . This is due to the lack of response of students to the learning activities in the classroom. Lessons seem boring to most learners . Due to the method applied during this konfensianal make learners saturated . Improved learning outcomes of students in learning the history of the Islamic Propagation jigsaw cooperative method in the high category , as it can reach above 80 % and the activity of the better teachers in the classroom , the higher the learning outcomes obtained learners.